2020
DOI: 10.1111/pde.14252
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic evaluation of six children with diffuse capillary malformation and undergrowth

Abstract: Background: Diffuse capillary malformation with overgrowth (DCMO) has been well described. However, capillary malformation with undergrowth (CMU) has been less reported in the literature. Objectives: We sought to describe the clinical features and determine associated somatic mutations in patients with CMU. Methods: We searched our multidisciplinary vascular anomalies clinic database for patients with CMU. Girth and length limb measurements were performed. In case of discrepancies in length, long leg radiograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Somatic pathogenic variants associated with undergrowth in vascular lesions have been previously reported in PIK3CA, TEK, GNAQ, and GNA11 (Martinez-Glez et al, 2022). The association of mosaic variants in PIK3CA with capillary malformations with undergrowth was confirmed by another group (Cubir o et al, 2020).…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Somatic pathogenic variants associated with undergrowth in vascular lesions have been previously reported in PIK3CA, TEK, GNAQ, and GNA11 (Martinez-Glez et al, 2022). The association of mosaic variants in PIK3CA with capillary malformations with undergrowth was confirmed by another group (Cubir o et al, 2020).…”
Section: Introductionmentioning
confidence: 64%
“…Pathogenic variants in several genes have been implicated in CM with undergrowth. Undergrowth with vascular lesions was observed in patients who had somatic pathogenic variants in PIK3CA , TEK , GNAQ , and GNA11 (Cubiró et al, 2020; Martinez‐Glez et al, 2022). Interestingly, somatic pathogenic variants in PIK3CA more commonly cause overgrowth (Cubiró et al, 2020; Lee et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Other than hearing loss, the patients reported here had no additional clinical characteristics reported to be associated with the GRHL2 genetic defect, such as diffuse capillary malformations and undergrowth [29], ectodermal dysplasia [9], or eye abnormalities [28]. Recent studies have also demonstrated the role of the GRHL family of proteins in carcinogenesis, as reviewed in [32,33], specifically GRHL2 in human breast cancer [34].…”
Section: Discussionmentioning
confidence: 79%
“…GRHL2 is a transcriptional factor [5], so those domains are crucial for its function. The majority of hearing-loss-related variants are truncating variants, while missense and deep intronic variants seem to be more likely to be associated with other GRHL2-related pathologies [9,10,[28][29][30]. In zebrafish, loss of GRHL2b induces midbrain-hindbrain boundary and otic vesicle defects [31].…”
Section: Discussionmentioning
confidence: 99%
“…There are just a few single reported patients, including a previous description of the patient MV00880 17 and small series 18 Combining the type of vascular malformation with molecular defects we identified in our cohort three different groups: undergrowth associated with (1) a capillary malformation (8.1%), ( 2) venous (32.4%), or combined venous-capillary malformation (36.8%), and…”
Section: Discussionmentioning
confidence: 80%